2019
DOI: 10.1016/j.ijscr.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

A rare case report of ascending colon perforation secondary to acute pancreatitis

Abstract: HighlightsKnowledge about colonic perforation secondary to acute pancreatitis has been limited to a few case reports, thus diagnostic and management dilemmas continue to persist.The exact pathogenesis by which pancreatic pseudocysts rupture into the colon is unknown. There have been several purported theories.The management of colonic complications secondary to severe acute pancreatitis relies on a high index of suspicion, as the clinical presentation in non-specific, varied and can occur late in the disease p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Little has been reported on descending colon pathology in association with AP: case of stenosis after severe AP [ 7 ] and case of stercoral perforation [ 8 ] . Recently, Dhadlie [ 9 ] report one case of ascending colon perforation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little has been reported on descending colon pathology in association with AP: case of stenosis after severe AP [ 7 ] and case of stercoral perforation [ 8 ] . Recently, Dhadlie [ 9 ] report one case of ascending colon perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical intervention with colon resection may be difficult, complicated and associated with higher risk of mortality, it should be reserved only for nonviable colon. In Aldridge series [ 9 ], ten patients had colon resection and six of them resection may be not necessary (histopathological examination showed only pericolitis).…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that the morbidity and mortality of gallbladder perforation are 37.5% and 12.5%, respectively[ 4 ]. Gastrointestinal fistula most commonly occurs in the colon, with an incidence of 3.3% in acute pancreatitis (AP) and 15% in SAP[ 5 ], which can also involve the duodenum, stomach, and small intestine[ 6 ]. Compared with patients without colon complications, SAP patients with colon involvement have significantly higher morbidity and mortality (54% for colonic necrosis)[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute gallstone pancreatitis' recurrence is related to the utilization of healthcare resources and significant morbidity. Therefore, cholecystectomy should be performed during hospitalization after every case of AP (Dhadlie & Ratnayake, 2019).…”
Section: Introductionmentioning
confidence: 99%